(3CdMGf GdShGLY Hjf GdHGOj hGdeQGLYs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3abO cfJ bOjekG LeYJ cJGHj GdPj hSeJg HGdeLGQGI hGdoeMGRGI hbO CMHHJ GdBf Cf CLeY eG OGQ Hjfj hHjf aVdGA YUQj eeG HOCJ ajg hQGLYJ s
(3BNQgG (B:s
(3jG ef SeG Hjf GdhQi brOQg CcTa dfG Yfg hYf CUdg s
(3HChdgG agQSJ HCSeGA ef hQO HgG ef GdQLGds
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdCOHs